2007
DOI: 10.2165/00044011-200727070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Massive Thrombosis of Brachiocephalic Veins and Superior Vena Cava Syndrome in a Patient with Non-Small Cell Lung Cancer Treated with the Epidermal Growth Factor Receptor Inhibitor Erlotinib

Abstract: The superior vena cava (SVC) syndrome occurs when obstruction of this vessel interrupts venous return of blood from the head, upper extremities and thorax to the right atrium. Most cases of SVC syndrome result from neoplasia, especially from lung cancer, but other non-cancer-associated causes may include fibrosis caused by radiotherapy, collagen-vascular diseases, arteriovenous shunts or thrombosis as a complication of use of central venous catheters or devices. We report here the case of a 60-year-old woman w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is unfortunate that we did not obtain information about the presence or lack of somatic mutation in the EGFR gene of the tumor, just as in a previously reported case,8 as this has been associated with a higher responsiveness to erlotinib 11. We were limited by the biopsy sample volume and by the need to treat the SVC obstruction, as EGFR gene sequencing usually takes 1 to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unfortunate that we did not obtain information about the presence or lack of somatic mutation in the EGFR gene of the tumor, just as in a previously reported case,8 as this has been associated with a higher responsiveness to erlotinib 11. We were limited by the biopsy sample volume and by the need to treat the SVC obstruction, as EGFR gene sequencing usually takes 1 to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Erlotinib has been used to treat NSCLC patients with SVC syndrome in the past,7,8 and the tumors in these cases completely responded to the erlotinib. In one of these cases,7 erlotinib was used concurrently with stereotactic body radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Cadman et al showed that proximally-placed CVC (proximal third SVC or thoracic inlet veins) are 16 times more likely to thrombose than the ones placed distally(distal third of the SVC or right atrium) [3]. In case of malignancy, the pathogenesis of thrombus formation in the SVC can be complex related to many factors such as humoral ones, mechanic obstruction, or even fibrosis caused by radiotherapy [4]. Collagen vascular diseases and Behçet's disease are among rare risk factors for SVC thrombosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment mainstay is made of low molecular weight heparin or vitamin K antagonists such as warfarin. In life-threatening situations however, thrombolytic therapy is used to dissolve massive clots obstructing the superior vena cava and its tributaries [4]. Placing SVC filters is very controversial and carries the risk of severe complications such as cardiac tamponade, pneumothorax, SVC perforation, or filter migration [16].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, superior vena cava syndrome has been reported following initiation of erlotinib therapy [5]. Patients may present with cyanosis and dyspnea.…”
mentioning
confidence: 99%